2015
DOI: 10.3109/09553002.2015.1012306
|View full text |Cite
|
Sign up to set email alerts
|

Associations of DNA-repair gene polymorphisms with a genetic susceptibility to ionizing radiation in residents of areas with high radon (222Rn) concentration

Abstract: As a result of this study, the elevated frequency of cytogenetic damage in people with particular DNA-repair gene polymorphisms in response to chronic exposure to radon was demonstrated. It was shown that the genes and corresponding polymorphisms (the XpG gene Asp1104His polymorphism, the ADPRT gene Val762Ala polymorphism and the NBS1 gene Glu185Gln polymorphism) can be used as molecular genetic markers of increased individual radiosensitivity in long-term residents of areas with high concentrations of radon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 50 publications
(43 reference statements)
0
9
0
Order By: Relevance
“… 15 Recent articles have demonstrated an increased frequency of cytogenetic damage in people with DNA-repair gene variations related with chronic exposure to radon and have indicated that ADPRT and NBS1 can be utilized as molecular genetic markers of increased radiosensitivity to long-term exposure to high concentrations of radon. 16 , 17 Another study suggested that radon exposure in never smokers seems to be a risk factor for lung cancer and that LCINS subjects diagnosed at a younger age might have been exposed to higher indoor radon concentrations, indicating an accumulative effect for radon levels on lung cancer features. 18 …”
Section: Introductionmentioning
confidence: 99%
“… 15 Recent articles have demonstrated an increased frequency of cytogenetic damage in people with DNA-repair gene variations related with chronic exposure to radon and have indicated that ADPRT and NBS1 can be utilized as molecular genetic markers of increased radiosensitivity to long-term exposure to high concentrations of radon. 16 , 17 Another study suggested that radon exposure in never smokers seems to be a risk factor for lung cancer and that LCINS subjects diagnosed at a younger age might have been exposed to higher indoor radon concentrations, indicating an accumulative effect for radon levels on lung cancer features. 18 …”
Section: Introductionmentioning
confidence: 99%
“…Finally, a number of studies have examined the effect of genetic polymorphisms of DNA damage repair genes in the outcome of individuals exposed to radon. For instance, individuals with a polymorphism leading to the Asp1104His substitution of DNA repair gene ERCC5 (XpG) displayed a higher frequency of micronuclei in their lymphocytes, representative of elevated cytogenetic damage and decreased radiosensitivity [116]. Alternatively, the absence of GSTM1 and GSTT1, members of the glutathione-s-transferase enzyme family-critical to detoxification and excretionis associated with an increased risk of lung cancer development [117,118].…”
Section: Prominent Cancer Genes Affected By Radonmentioning
confidence: 99%
“…Sinitsky MY et al suggested the elevated frequency of cytogenetic damage in people with DNA-repair gene polymorphisms due to chronic exposure to radon and XpG, ADPRT, and NBS1 gene can be used as molecular genetic markers of increased individual radiosensitivity in long-term residents with high concentrations of radon [ 39 ]. Another report suggested GSTM1 and GSTT1 genes deletion increase the risk of lung cancer and these genes might regulate the carcinogenic pathway by radon radiation [ 40 , 41 ].…”
Section: Radon Exposure and Genetic Factorsmentioning
confidence: 99%